(3dWGFa GdETGQGJ aj ObGFb GdYHGQGJs - (3CHh GdbGSe YHO GdcQje GdbTjQj,J (B465 (3g` s ((3GHh Ydi Hf SYO Hf gHI Gddg Hf SYO s)
(3ChdgG (B:s
(3GdMeO ddg GdPj TQM GdbdhH ChdjGAI aGJMI GdcJGH gPg GdShQI JSej aGJMI GdcJGH heaGJMg s
(3BNQgG (B:s
(3hjbGd (B: (3GdYed GdUGdM GYJbGO LhGR GdaQMI Je GdeLdO GdChd ef GdCUd hgh GdTQW GdChd s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdJUha hGdBOGH GdTQYjIs